Kinetics of Iodination of Benzenes and Their Reactivity - Joel Karunakaran, R.; Gopalan, R. (Asian Journal of Chemistry, 2010)
The kinetics of iodination of benzenes have been investigated with the iodinating sytems A: I2—NaNO2—HNO3 and B: I2—H2SO4— HNO3 separately. The data obtained from such studies show the following common features with both the systems: (a) The order of the reaction is 0.5 in [I2]. (b) The reaction shows adominant substituent effect. (c) The reactivity order is m-xylene > o-xylene > p-xylene > toluene> benzene> iodobenzene > bromobenzene > nitrobenzene > chlorobenzene > fluorobenzene. The activation parameters have been evaluated for each substrate. Analysis of these parameters indicates the involvement of a bulky transition state. A mechanism involving the attack of the benzene by the electrophilic iodine species has been suggested. The iodination involves the initial formation of electrophile HNO2I+ in system A and I+ in system B.